Innovative Cash Accounting Information System Design for Agrotourism Hotel in Batu City (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to design an effective cash accounting information system for an agrotourism hotel in Batu City. The data collection methods used are field studies and literature review, employing techniques such as observation, interviews, and documentation. The important significance of this research is to enhance the cash receipt procedures for hotel room rental payments by incorporating additional digital payment methods through e-wallets and QRIS, thereby increasing transaction efficiency that benefits both the hotel and consumers. The significant importance of this research is to enhance the efficiency of payment transactions, making it easier for both the hotel and consumers. The qualitative analysis in this study aims to improve the accuracy of cash recording, reduce the risk of errors and misuse of funds, enhance internal control, broaden payment options, and provide practical guidance for hotels and consumers regarding payment and cash receipt procedures. With improved cash receipt procedures, the hotel will be better prepared to meet consumer needs and increase competitiveness in response to changes.